Measuring Treatment Readiness Among Patients With Opioid Use - Washdev Washdev; Muhammad Ilyas Jat; Fatima Taufeeq; Muhammad Tarique Arain; Saba Yasein; Shaoib Ahmed (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College, 2020)
Objective: To measure treatment readiness in patients with opioid use in the form of problem reorganization, desire for help and taking steps. Methodology: This was a descriptive and cross-sectional study, conducted at the Institute of Behavioral Sciences (IBS), Dow University of Health Sciences (DUHS), Karachi, Pakistan. The duration of the study was from 1st January 2018 to 1st June 2018. Those patients who fulfilled the criteria of the dependent on opioids as per the International Classification of Diseases version 10 (ICD-10) were enrolled in the study. Those who were using substances other than opioids such as Cannabis or having organic brain disorder such as dementia were excluded from the study. Treatment readiness was measured by The Stages of Change Readiness and Treatment Eagerness scale (SOCRATE). The collected data were analyzed by Statistical Package for the Social Sciences (SPSS) version 22.0. Results: Of the 120 participants, 96 (80%) were males while 24 (20%) were females. Mean age of the patients was 31.57 ± 8.71 years. Among all 48 (40%) were married. Majority of patients 54 (52.9%) were employed. Almost two-thirds were in favour of the strongly agree option as per the Stages of Change Readiness and Treatment Eagerness Scale. While talking about ambivalence 54% strongly agreed that they were ambivalent about their addiction. Twenty-one per cent strongly agreed that they have taken steps to quit. Statistically age group, gender, marital status, educational status and occupational status were not significant. Conclusion: As the Stages of Change Readiness and Treatment Eagerness scale, mostly opioids users strongly agree for treatment as well as recognition of their problems and desire for change.